The illustrated guide to cows : how to choose them, how to keep them - Lewis, Celia, 1948- (Bloomsbury, 2014)
Cows are one of the most undemanding domestic animals to keep, being mainly healthy and temperate, and keeping cattle as a smallholder can be a very rewarding enterprise, supplying you with food and milk and helping with the management of grassland on your property. Celia Lewis's charmingly illustrated and informative book is perfect for those interested in keeping a cow or two and choose the best breed for their circumstances.